Development of Nearpod-Based Learning Media to Improve Learning Outcomes in Elementary School Grade V IPAS Subjects - Oktavia Eka Darnawati; Sigit Yulianto (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this research is to develop Nearpod-based learning media to help improve students’ low learning outcomes and maximize the use of technology-based media at SDN Wonosari 02 Semarang City. This research is a type of Research and Development (R&D) research with the ADDIE development model. The results showed that Nearpod-based learning media is very feasible to use in learning IPAS human respiratory system material with a percentage of assessment by material experts of 88.75% and media experts of 93.75%. The results of the questionnaire assessment by teachers related to the media obtained a percentage score of 90% and students of 93.33% with a very feasible category. For the Paired Sample T-Test test with a significance value of sig. (2-tailed) obtained a result of 0.000. So, it is known that the value is < 0.05. Therefore, it can be concluded that there is a significant difference from the average pretest score and the average posttest score. As for the N-Gain Test, the score shows an average of 0.71 with high criteria. The conclusion of this study is that Nearpod media is feasible and effective to improve student learning outcomes in IPAS learning.